Investigating the relationship between the HJHS and HAL in routine clinical practice: A retrospective review. Issue 6 (8th October 2018) - McLaughlin, Paul; Morris, Richard; Chowdary, Pratima
Abstract: Introduction: Comprehensive musculoskeletal assessment for monitoring joint health in haemophilia includes both physical assessment with Haemophilia Joint Health Score (HJHS) and assessment of self‐reported function by Haemophilia Activities List (HAL). Methods: Correlation between physical assessment and joint function was undertaken between HJHS and HAL in patients with SHA and SHB who had both assessments at the same visit over a one‐year period. Results: Data from 120 patients (96‐SHA/24 = SHB) with a median age 33 years (range 19‐73) were included. Median total HJHS was 19, increasing with age: 18‐30 years—7, 31‐50 years—25 and 51‐73 years—44. Similarly, median total HAL score was 80 with decreased function associated with increasing age: 18‐30 years—90.4, 31‐59 years—71.7, 51‐73 years—49.5. Median Total HJHS and HAL demonstrated strong correlation ( r s  = 0.66, P  < 0.01). Moderate‐to‐strong correlations were seen across the entire age group between the HJHS LL and UL subtotals and corresponding limb HAL domains. Within age groups, correlations were less significant particularly for the upper UL domains in HAL and the UL HJHS score. The wide range of ROM in joints categorized as markedly affected (ie, ROM loss score = 3) highlights the potential ceiling effect of this domain score and its use in chronically damaged joints. Conclusion: HJHS and HAL showed moderate‐to‐strong correlation with discrepancy in some individual patients. Prospective studies are required to better understand the clinical utility of both especially in severe joint disease where HAL may have a potential advantage.